Child-parent agreement on alcohol-related parenting: Opportunities for prevention of alcohol-related harm - Shaw, T.; Johnston, R.; Gilligan, C.; McBride, Nyanda; Thomas, L. (Australian Health Promotion Association, 2018)
© 2018 Australian Health Promotion Association. Issue addressed: Excessive alcohol consumption places adolescents at increased risk of preventable, acute alcohol-related injury. Parental attitudes and behaviours influence adolescents' alcohol use. This study examined alignment in parent and child reports of alcohol-related parenting and whether misalignment related to the child ever having drunk alcohol. Methods: A cross-sectional online survey was conducted in 5 secondary schools in [information removed for blinding in Perth, Western Australia] in 2015. All students in Years 7, 10 and 12 and their parents were eligible, and data were matched for 124 child-parent dyads. Alignment of parent-child reports was assessed using kappa statistics. In dyads where the parent reported protective attitudes and behaviours, the association between misalignment and alcohol use was tested in logistic regressions. Results: Overall, child-parent reports were aligned on parents' expectations, knowledge and actions (65% and higher agreed). While alignment on parental expectations seemed to decrease with age, alignment on parental communication and rule-setting increased. Misalignment on reports of parents' expectations was associated with increased odds of the child reporting having ever had alcohol (OR = 5.5; 95% CI = 2.7-47.7), as was parental supply (OR = 20.2; 95% CI = 3.3-121.5), but misalignment on parental communication, rule-setting and knowledge were not. Conclusions: Parent non-supply of alcohol and disapproval of use were most important in terms of associations with ever drinking. So what?: These findings call for interventions that support parents to expect no alcohol use and enable parents to communicate their expectation in a manner that resonates with their child. Effective parenting will contribute to reducing alcohol-related harm in adolescents.